IFRA: instruction footprint recording and analysis for post-silicon bug localization in processors - Park, Sung-Boem; Mitra, Subhasish (2008 45th ACM/IEEE Design Automation Conference, 2008)
The objective of IFRA, Instruction Footprint Recording and Analysis, is to overcome the challenges associated with a very expensive step in post-silicon validation of processors -- bug localization in a system setup. IFRA consists of special design and analysis techniques required to bridge a major gap between system-level and circuit-level debug. Special hardware recorders, called Footprint Recording Structures (FRS's), record semantic information about data and control flows of instructions passing through various design blocks of a processor. This information is recorded concurrently during normal operation of a processor in a post-silicon system validation setup. Upon detection of a problem, the recorded information is scanned out and analyzed for bug localization. Special program analysis techniques, together with the binary of the application executed during post-silicon validation, are used for the analysis. IFRA does not require full system-level reproduction of bugs or system-level simulation. Simulation results on a complex super-scalar processor demonstrate that IFRA is effective in accurately localizing bugs with very little impact on overall chip area.